2021
DOI: 10.1142/s0217751x21500044
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of spherical collapse in energy–momentum squared gravity

Abstract: This paper investigates the dynamics of spherical collapse in the framework of energy–momentum squared gravity. This theory overcomes the big-bang singularity and provides viable cosmological consequences in the early time universe. We proceed our work by considering the nonstatic spherically symmetric space–time in the interior and static spherically symmetric metric in the exterior regions of the star. The Darmois junction conditions between interior and exterior geometries are derived. We construct dynamica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…[ 34 ] We have also discussed the dynamics of celestial objects and found that collapse rate reduces in EMSG as compared to GR. [ 35 ] The physical features of a gravastar in this framework has been studied in [36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…[ 34 ] We have also discussed the dynamics of celestial objects and found that collapse rate reduces in EMSG as compared to GR. [ 35 ] The physical features of a gravastar in this framework has been studied in [36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast to most higher-order theories of gravity referred to as f (R) theories, where the gravitational Lagrangian is modified as a nonlinear function of the Ricci scalar curvature R, in EMSG, the higher order of the energy-momentum tensor of the matter fields is considered to modify the general relativity (GR). This theory has recently been taken into consideration and examined in several contexts [7][8][9][10][11][12][13][14]. Moreover, applying some observational measurements, its free parameter has been constrained, e.g., see [3,4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Sharif and Gul [34] explored the structure of cosmic objects through the Noether symmetry approach. They also studied the dynamics of cylindrical collapse with dissipative matter in the presence of charge and deduced that the dissipative matter, electromagnetic field and modified terms reduce the collapse rate [35].…”
Section: Introductionmentioning
confidence: 99%